The Role of the Exchange Rate Regime in the Process of Real and Nominal Convergence - Gaetano D'Adamo; Riccardo Rovelli (Institute for the Study of Labor (IZA), 2013)
During the last decade, economists have intensively searched for evidence on the importance of the Balassa-Samuelson (B-S) hypothesis in explaining nominal convergence. One general result is that B-S can at best explain only part of the excess inflation observed in the European catching-up countries, which suggests that other factors may be at play. In these and related studies, however, the potential role of the exchange rate regime in affecting price convergence in Europe has been overlooked. In this respect, we claim that the choice of the exchange rate regime has decisively affected the path of nominal convergence. To show this, we first model the (endogenous) choice of the exchange rate regime and, in a second stage, estimate a B-S type of regression for each regime. Our results show that, for countries which pegged to or adopted the euro, the effect of the same increase in the dual productivity growth (that is, the difference in productivity growth between the traded and non-traded sectors) on the dual inflation differential is more than twice as large as that in the flexible countries. We conclude that, in a catching-up country, premature euro adoption may foster excess inflation, beyond that which is to be expected as a consequence of productivity convergence on the basis of the B-S effect.
Keywords: C34; E52; F31; 330; exchange rate regimes; Balassa-Samuelson effect; inflation; euro adoption